Suor Angelica - (:unkn) unknown (My University, 2015)
The Royal Irish Academy of Music in collaboration with The Lir National Academy of Dramatic Art at Trinity College Dublin presents Suor Angelica, an opera by Giacomo Puccini (1858-1924). Original libretto by Giovacchino Forzano (1884-1970). Suor Angelica is the second opera of the trio of operas known as Il Trittico (Triptych). March 3rd (Preview), 5th, 6th and 7th, 2015 at 6.30 pm at the Abbey Theatre on the Peacock stage. Conducted by Andrew Synnott. Directed by Tom Creed.
Opera programme
Keywords: Opera; Concert programmes; Operas; Puccini, Giacomo, 1858-1924; Puccini, Giacomo, 1858-1924 - Suor Angelica